Managerial Ability, Real Earnings Management, and Earnings Quality - Alex Johanes Simamora (LPPM Universitas Terbuka, 2021)
This research aims to examine the effect of managerial ability on real earnings management and earnings quality, and the role of higher ability managers between real earnings management and earnings quality. The total sample includes 846 manufacturing firms-years for the research period 2008-2016. Real earnings management is measured by abnormal activities of over-sales, over-production, and discretionary expenses cutting. Data analysis uses the fixed-effect model of earnings persistence, and fixed-effect model of earnings value relevance and predictability. The results show that higher ability managers use their knowledge, skill, and expertise to perform real earnings management and to increase earnings quality. Since real earnings management can reduce earnings quality, high-ability managers engage more in efficient than opportunistic real earnings management to increase earnings quality. This research provides comprehensive evidence of the relationship between managerial ability, real earnings management, and earnings quality since there is a findings gap between managerial ability and earnings management, as well the gap between earnings management and earnings quality.